Existence and determination of competitive equilibrium in unit commitment power pool auctions price setting and scheduling alternatives. - Madrigal, M. (IEEE Transactions on power systems)
The existence, determination and effects of competitive market equilibrium for unit commitment power pool auctions are investigated in this paper. When an equilibrium does not exist, under specific situations, conflictive multiple optimal primal solutions may exist. When an equilibrium exists, multiple primal solutions do not represent conflicts of interest. The existence or nonexistence of competitive equilibrium can be determined if the dual problem is solved to optimality. If equilibrium does not exist, there is excess supply at the optimal dual solution, which can be used to define priority orders and price setting alternatives to determine a final schedule, and avoid the conflicts of interest and revenue deficiency. Under disequilibrium, the optimal dual variables are not market clearing prices; a nonuniform pricing rule that avoids the flaws and complications of other pricing rules, such as maximum average cost and price minimization auctions, is proposed in the paper. The proposed scheduling and price-setting alternatives show that unit commitment models can be used in a market environment